Effect of Bleaching Agents on Healthy Enamel, White Spots, and Carious Lesions: A Systematic Review and Meta-Analysis - Grigoria Gkavela; Vlassios Kakouris; Eftychia Pappa; Christos Rahiotis (MDPI AG, 2024)
This systematic review examines studies focusing on tooth bleaching and its effects on healthy enamel or incipient caries and bacterial adhesion. The aim is to explore the impact of different bleaching agents on incipient caries lesions and healthy enamel. Clinical studies, in vitro studies, and observational studies that compared at least two groups were included. A search strategy was used to select studies from the MEDLINE via Pubmed and Scopus databases. Two evaluators performed data extraction, screening, and quality assessment independently. Only studies written in English were included. From 968 initial records, 28 studies were selected for a full-text evaluation. Of these, 7 studies were classified as cluster 1 (bacterial adherence on teeth), 12 studies as cluster 2 (no bacteria involved), 4 studies as cluster 3 (no teeth deployment), and 5 clinical studies were cluster 4. Of the selected studies, 6 (21.4%) supported increased bacterial attachment capacity and cariogenic dynamics, 4 (14.3%) decreased adhesion and cariogenic activity, 7 (25%) showed no difference, and 11 (39.3%) followed a different methodological approach and could not be categorized. The risk of bias appeared to be high, mainly because of the different methodologies in the studies, so we cannot reach a confident conclusion. Nevertheless, as far as carbamide peroxide bleaching is concerned, there does not seem to be a clinically significant alteration, neither in microorganism counts nor in enamel microstructure.